UTILIZATION OF SONG LYRICS IN “TIKTOK” IN TEACHING VOCABULARY FOR SENIOR HIGH SCHOOL STUDENTS - Diky Ari Pratama; Yunik Susanti; Suhartono (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Mastering English vocabulary has its own challenges, especially in Indonesia where English is a foreign language. To help students master vocabulary, educators need to design interesting learning media. The researcher have used the "TikTok" application as an innovative medium to create a fun learning atmosphere. The research aims to determine students' vocabulary mastery before and after using the application and how significant its influence is on students at SMAN 6 Kota Kediri. The researcher used quantitative research with one group pre-test and post-test. The data results show that the t-score is higher than the t-table at the 5% significance level. The average pre-test score was 68.38, and the average post-test score was 81.67. The t-test calculation shows that there is -8.540 with a degree of freedom of 30 and significance smaller than 0.05. It can be concluded that t-test is higher than t-table Ha is accepted. So, the research results show that there is a significant influence on treatment, because the post-test score is higher than the pre-test score. These results show that the use of song lyrics in the "TikTok" application can help students solve learning problems, especially in mastering students' vocabulary.